Toward Sustainable and Energy Efficient Urban Transport - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2015)
Many cities of developing countries are experiencing rapid growth of motorized transportation. This is leading to severe congestion, which, in turn, is reducing productivity. Road accidents have been increasing. Transport emissions have become a major contributor to severe air pollution and greenhouse gas emissions. The main cause of these problems has been the increasing preference for personal motor vehicles for commuting to work and getting around the city. In many countries, urban development practices have worked in favor of such preference, leading to urban sprawl. Thus, remedial measures have to focus on reversing the preference for such modes of travel, shifting to public transport, cycling, or walking, and building and retrofitting cities to minimize the need for private automobiles. The objective of this guidance note is to present a systematic, practical, and comprehensive approach to dealing with the problems of urban transport. It outlines a framework of possible interventions and demonstrates how such interventions relate to the overall objectives of improving mobility and energy efficiency as well as reducing air pollution and road accidents. Thereafter, it highlights a range of cross-cutting issues that need to be addressed and also suggests steps to create an enabling environment to move towards a sustainable urban transport system. Its target audience is the city-level leadership and key decision makers responsible for sustainable urban mobility.